Application of Light Scattering Techniques to Nanoparticle Characterization and Development - Carvalho, Patrícia M.; Felício, Mário R.; Santos, Nuno C.; Gonçalves, Sónia; Domingues, Marco M. (Frontiers in Chemistry, 2018)
Over the years, the scientific importance of nanoparticles for biomedical applications has increased. The high stability and biocompatibility, together with the low toxicity of the nanoparticles developed lead to their use as targeted drug delivery systems, bioimaging systems and biosensors. The wide ranges of nanoparticles size, from 10 nm to 1 µm, as well as their optical properties, allow them to be studied using microscopy and spectroscopy techniques. In order to be effectively used, the physicochemical properties of nanoparticle formulations need to be taken into account, namely, particle size, surface charge distribution, surface derivatization and/or loading capacity and related interactions. These properties need to be optimized considering the final nanoparticle intended biodistribution and target. In this review, we cover light scattering based techniques, namely dynamic light scattering and zeta-potential, used for the physicochemical characterization of nanoparticles. Dynamic light scattering is used to measure nanoparticles size, but also, to evaluate their stability over time in suspension at different pH and temperature conditions. Zeta-potential is used to characterize nanoparticles surface charge, obtaining information about their stability and surface interaction with other molecules. In this review, we focus nanoparticle characterization and application in infection, cancer and cardiovascular diseases.